Legal Certainty of Application for Marriage Registration of Non-Religious Couples After the Issuance of Supreme Court Circular Letter No. 2 of 2023 - Muthiah, Ghina Khansa; Dewi, Amelia Sri Kusuma; Widhiawati, Dyah (The Islamic Education and Multiculturalism Foundation, 2024)
This research focuses on analyzing specifically whether the regulation of different religions after the issuance of SEMA Number 2 of 2023 has fulfilled legal certainty. Marriage is not only an agreement between two individuals, but also a form of worship recognized by society and the state. Therefore, the rules for the implementation of marriage have been regulated by the state in Law Number 1 of 1974 concerning Marriage. However, it will cause problems if the marriage recorded in the civil registry is actually categorized as an invalid marriage, one of which is a marriage of different religions. In contrast to the explanation in Article 35 of the Civil Registration Law that the registration of valid marriages, including marriages between people of different religions that have been determined by the Court, is an obligation. With the disharmony between the two laws, it can affect judges in adjudicating cases of applications for registration of marriages between people of different religions and beliefs. To answer the existing problems, the author uses normative juridical research with a statutory approach method (statue approach), conceptual approach (conceptual approach). Primary, secondary, and tertiary legal materials and using grammatical and systematic interpretation. The issuance of SEMA Number 2 Year 2023 is a legal instrument issued by the Supreme Court. This SEMA is expected to create a more structured and reliable judicial system. It is important to evaluate the consistency and harmony in the application of laws related to interfaith marriage after the issuance of the SEMA.